Integrated nutrient management in maize (Zea mays)-wheat (Triticum aestivum) sequence under rainfed condition in Himachal Pradesh - MAHAJAN, K K; SINGH, RANJODH; SHARMA, V K; ACHARYA, C L; DEOR, B S; GOYAL, N K; MASAND, S S (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during 1991-92 to 1994-95 on fixed sites in different agro-climatic zones of Himachal Pradesh to study the effect of different combinations of N, P and K in the presence and absence of farmyard manure on maize (Zea mays L.) - wheat (Triticum aestivum L. emend. Fiori & Paol.) system. In sandy loam soil (Udifluvent) the response of P was not observed in the presence as well as absence of farmyard manure but was observed on wheat in the absence of farmyard manure only. In coarse soil (Ustipsamment) the response ofP was found in both maize and wheat in the presence and absence of farmyard manure. In sandy loam soil (Hapludalt) the addition of P was useful in the absence of farmyard manure only, but in clay loam soil (Ustochrept) there was no effect of P application. Application of 45 kg N/ha + farmyard manure for maize crop followed by 25-30 kg N/ha in the absence or presence of farmyard manure for wheat crop was in general as good as 90 kg N/ha and 50-60 kg N/ha respectively. The addition of K was beneticial in only coarse soils. In general NP (140 to 150 + 30.5 to 37+ 10 tonnes farmyard manure has given the maximum return.